Dampak Pelatihan Guru Terhadap Penerapan Teknologi dalam Pengajaran di SMPN 3 Peureulak - Afwiyah (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2023)
This research aims to reveal the impact of teacher training on the application of technology in teaching at SMPN 3 Peureulak schools. A qualitative approach was used in this research, by conducting interviews and observations of teachers who had taken technology training. The research results show that teacher training has a positive impact on increasing their understanding and skills in utilizing technology in the classroom. Teachers who have undergone training tend to be more innovative in designing and implementing learning, creating a learning environment that is more dynamic and responsive to student needs. Thus, this research contributes to further understanding of the importance of teacher training in the context of technology implementation in junior high schools. The implications of these findings can be the basis for developing more effective policies and training programs, so that they can continue to improve the quality of education at SMPN 3 Peureulak through optimal use of technology in teaching.